Pengaruh Corporate Social Responsibility, Corporate Image, dan Competitive Advantages Terhadap Economics Performance - Ahmad Pebrian; Dirvi Surya Abbas; Hesty Erviani Zulaecha (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to determine the effect of Good Corporate Governance, Profitability, Leverage, and Fixed Asset Intensity on Tax Avoidance in manufacturing companies. The research time period used is 5 years, namely the 2017-2021 period. The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sampling technique used was purposive sampling. Based on the established criteria 47 companies were obtained. The ana;iytical method used is [ane; data regression analysis using Eviews 12. The results show that Institutional Ownership and Leverage had no effect on Tax Avoidance, Audit Committee, Profitability, Fixed Asset Intensity, and Fixed Asset Intensity with Tax Avoidance. .